Adaptations of Cetacean Retinal Pigments to Aquatic Environments - Fasick, Jeffry I.; Robinson, Phyllis R. (Frontiers in Ecology and Evolution, 2016)
The underwater environment places unique constraints on the vision of cetaceans compared to their terrestrial mammalian counterparts. Water absorbs and filters light affecting both the intensity and spectral distribution of light available for vision. Therefore, the aquatic environment restricts the spectral distribution of photons and limits the distance at which objects may be observed. The cetacean eye possesses numerous anatomical, cellular and molecular adaptations to the underwater light environment that increase photon capture in a light-limited environment. These adaptations include a powerful spherical lens, a unique corneal design allowing for acute vision in both air and water, as well as a blue reflective optic tapetum. There are also molecular adaptations that influence the spectral sensitivity of both the rod and cone visual pigments. The spectral sensitivities of cetacean retinae have been a focus of attention over the last two decades. While most terrestrial mammals have dichromatic color vision based on two classes of cone photoreceptors, all cetaceans lack cone based color vision. For example, the Delphinidae (dolphins), Phocoenidae (porpoises), and some members of Ziphidae (beaked whales) possess single rod and cone photoreceptor classes. Recently, rod monochromats were identified in Ziphidae, Physeteroidea, and almost all of the mysticete (baleen) whales. The absorbance spectra of cetacean rod visual pigments are spectrally tuned to the available radiance spectra at foraging depths with an inverse relationship observed between the wavelength of maximum sensitivity of the rod pigment and depth. This also holds true for the spectral tuning of long-wavelength sensitive cone visual pigments in cetaceans. Cetacean melanopsins, the visual pigment expressed in a small subset of ganglion cells in mammalian retinae, have only just recently been examined in the cetacean rod monochromats. Genetic analyses coupled with molecular modeling predict that cetacean melanopsins possess nearly identical absorption spectra compared to their terrestrial mammalian counterparts. However, it appears that the melanopsins from the cetacean rod monochromats may possess a mechanism that inhibits relatively rapid deactivation of the light-activated melanopsin. This mechanism would result in prolonged pupil constriction resulting in a very useful mechanism in the prevention of photobleaching of rod pigments under photopic conditions.